The Inhibition Activity of Silver Nanoparticles Compared with D-Glycin and Imipenem Effect on the Biofilm Formation by Food-origin Salmonella - Al-Khafaji, Marwa H. M. (Iraqi Journal of Science, 2022)
Since decades silver was depended worldwide as a treatment to a lot of diseasesranging from burn infections, anthrax, and typhoid fever to bacterial conjunctivitisin stillbirth, but its effectiveness against biofilms is still undetermined. Salmonella isa major cause of food poisoning outbreaks especially in the third world countries.Thus, in the present study; the antimicrobial activity of silver nanoparticles (Ag-NPs) against Salmonella enterica biofilm was examined; their activity wascompared with amino acid; D-Glycin and imipenem antibiotic. The result of thestudy revealed that Ag-NPs exhibited considerable antimicrobial property againstSalmonella enterica biofilm where the minimum inhibitory concentration (MIC)was found at 50 μg/ml while MIC of D-glycin and imipenem were 50mM and4μg/ml respectively. The isolates ability to form biofilm was assayed using thetissue culture plate (TCP) assay, all the isolates were biofilm producers but with adifferent thickness degrees. It was found that both of Ag-NPs and imipeneminhibited Salmonella biofilm formation, but the inhibition by Ag-NPs was more thanthe antibiotic imipenem, whereas D-Glycin increased the ability of Salmonellaisolates to form biofilm.